SHIFTING IN THE MEANING OF THE DEBUS PERFORMANCE SPELL: THE ISLAMIC IDENTITY OF THE BANTEN COMMUNITY - Ezik Firman Syah; Novi Anoegrajekti; Nuruddin Nuruddin (Prosiding Seminar Nasional dan Internasional HISKI, 2023)
Debus Banten performing arts has a mantra in performing its rituals and performances. These mantras are used in the Jangjawokan debus school as a diversion for the Qodriyah and Rifa'iyah sects of debus, which do not use mantras according to the early spread of Islam in their performances. The use of mantras in the Jangjawokan genre debus certainly has meaning for each recited mantra. The purpose of this study is to describe the shift in the importance of the Debus Mantra as the Islamic identity of the Banten people. This study uses the Ethnographic method of the Spradley model with the perspective of cultural studies used to explain the Islamic identity of the Banten people in understanding the meaning of the Jangjawokan mantra debus. The results showed that the discovery of the spell when the to debus performance began by using Roland Barthes' Semiotic theory in expressing the meaning of the Jangjawokan debus mantra. Even though the Jangjawokan debus used mantras in their performances, Islamic values were still embedded in the mantras when the debus performances started. The recitation of prayers in the meaning of this mantra is intended to present the saints and prophets and ask for their help to keep the debus players from harm during the performance.